Competition in the public school sector: Evidence on strategic interaction among US school districts - Rincke, Johannes (Journal of Urban Economics, 2006)
This paper provides evidence on strategic interaction among local school districts. The analysis makes use of a significant change in the institutional environment for school districts in Michigan in 1996, when the state established a voluntary inter-district choice program. The school districts' participation decisions are modelled as discrete choice decisions using a spatial latent variable model. Strong effects are found saying that lagged adoptions of neighbors positively affect the current probability of participation. A simple test exploiting limitations of student mobility in inter-district transfers suggests that the driving force for interdependencies among adoption decisions was competition for students.
WiSo-Import:2015-03-26:1716
Keywords: strategic interaction; school districts; school choice; spatial probit